2018
DOI: 10.1101/355065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory T-cells are required for neonatal heart regeneration

Abstract: Previous work has elegantly demonstrated that, unlike adult mammalian heart, the neonatal heart is able to regenerate after injury from postnatal day (P) 1 to 7. Recently, macrophages are found to be required in the repair process as depletion of which abolishes endogenous regenerative capability of the neonatal heart. Nevertheless, whether innate immunity alone is sufficient for neonatal heart regeneration is obscure. source of chemokines and cytokines that attract monocytes and macrophages previously known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition, Tregs are indispensable for heart regeneration in neonatal mice, potentially by promoting monocyte/macrophage recruitment as well as CM proliferation (Fig. 4 ) [ 60 ] (a preprint article on biorxiv without peer-review). These data support an active role of Tregs in cardiac regeneration through immune modulation and the secretion of Neuregulin [ 46 ].…”
Section: Inflammationmentioning
confidence: 99%
“…In addition, Tregs are indispensable for heart regeneration in neonatal mice, potentially by promoting monocyte/macrophage recruitment as well as CM proliferation (Fig. 4 ) [ 60 ] (a preprint article on biorxiv without peer-review). These data support an active role of Tregs in cardiac regeneration through immune modulation and the secretion of Neuregulin [ 46 ].…”
Section: Inflammationmentioning
confidence: 99%
“…Over the past four years, much attention has been given to the immune response that immediately follows cardiac injury [10,20,22,25,26,44,45,46,47,48,49,50,51,52,53,54,55,56]. From these investigations, it is becoming clear that immune cells can greatly influence the course of the core cardiac repair program, controlling the balance between pro-fibrosis and pro-regeneration.…”
Section: Cardiac-injury Response Modulatorsmentioning
confidence: 99%
“…Macrophages and regulatory T cells (Tregs) are two prominent immune cells that have emerged as central players during heart regeneration. Functional studies from numerous groups have shown CM proliferation is suppressed under conditions of cell depletion [49,53,55]. However, the mechanism of action exerted on CMs and the potential influence on other immune cells are outstanding questions within the cardiac regeneration discipline.…”
Section: Cardiac-injury Response Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations